Efficacy and Toxicity of Different Forms of Asparaginases Against Acute Lymphoblastic Leukemia: A Review - Baral, Adesh; Gorkhali, Ritesh; Basnet, Amit; Koirala, Shubham; Bhattarai, Hitesh K (Nepal Journal of Biotechnology, 2021)
Acute lymphoblastic leukemia (ALL) is a form of blood cancer that affects white blood cells and is among the most common forms of leukemia with children and adolescents showing the highest number of cases. Most treatment protocols include chemotherapy using asparaginase. Asparaginase converts asparagine to aspartic acid and ammonia. Unlike normal, healthy cells, cancerous cells depend on asparagine for their growth. When these cells are deprived of asparagine by the action of the enzyme, the cancer cells selectively die. As of date, several forms of asparaginases are commercially available and are administered in ALL therapy. But due to limited study, it will be early and inaccurate to predict which forms of the enzymes are better. In this review, we aim to compare the efficacy and toxicity of four different asparaginases—native Escherichia coli asparaginase, PEG Escherichia coli asparaginase, Erwinia chrysanthemi asparaginase and a recombinant Escherichia coli asparaginase—used in ALL therapy in children and adolescents using available clinical trial data. PubMed and Clinical trial.org databases were used to select studies. Asparaginase activity, toxicity, anti-asparaginase antibody level and event-free, overall survival was compared for different asparaginases. Seventeen randomized and non-randomized controlled trials were included. Evidence was insufficient to ascertain which asparaginase is the best. PEG Escherichia coli asparaginase seems to be better with a high activity among the treated patients but there remains high toxicity for all available asparaginases. This study highlights a need to discover alternative sources of asparaginase from the organisms, which are evolutionarily distant from Escherichia coli and Erwinia chrysanthemi with high higher enzyme activity and reduced toxicity.